The development of gullies in a Mediterranean environment: The example of the Corgo gully (central Portugal) - B. Martins; A. Meira-Castro; A. Nunes; L. Lourenço (Energy Reports, 2020)
Gullies are the most energy-efficient way to transport excess runoff from the watershed after a landscape disturbance. The diversity of physical factors that are associated with gully formation makes straightforward interpretation difficult and requires well-founded analysis based on local observations. Some gullies have developed in the Alva river basin and some of them reach a spectacular size, especially in areas where forest fires have recurred with greater severity. In this paper, we identify the most important factors in the formation and development of the River Corgo's gully, located in the Alva river valley in central Portugal. The evolution of this gully in the last 4 years is also examined, based on a study of the modification of its morphological characteristics. The analysis was based on the Spearman-Rho correlation coefficient and stepwise multiple regression to estimate the correlation between the quantitative characteristics, geomorphological processes and biophysical variables. The results show that the main factors that seem to control the spatial variation of soil erosion are the soil penetration resistance, slope, slope shape and vegetation cover.
Keywords: 330; Centre of Portugal; Corgo; Gully; Soil erosion